2010
DOI: 10.1111/j.1532-849x.2010.00613.x
|View full text |Cite
|
Sign up to set email alerts
|

Resistance to Wear of Four Matrices with Ball Attachments for Implant Overdentures: A Fatigue Study

Abstract: Gold alloy and Teflon matrices showed the highest retention values without retention loss after 3 years of simulated function. Titanium and O-ring matrices presented a continuous loss of retention with the highest wear on the ball attachments when combined with the titanium matrix.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

12
48
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(62 citation statements)
references
References 21 publications
12
48
0
Order By: Relevance
“…[18][19][20] Routine procedure for the maintenance of ball attachments is mainly to adjust or replace the inefficiently retentive female components to compensate for wear. [11][12][13][14]19,23,24 However, the vast of these studies focused on the wear of the female components. It has been shown that both gold and titanium male components showed noticeable signs of abrasion after 8 years of clinical use.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…[18][19][20] Routine procedure for the maintenance of ball attachments is mainly to adjust or replace the inefficiently retentive female components to compensate for wear. [11][12][13][14]19,23,24 However, the vast of these studies focused on the wear of the female components. It has been shown that both gold and titanium male components showed noticeable signs of abrasion after 8 years of clinical use.…”
mentioning
confidence: 99%
“…21 However, this procedure may not be adequate to gain the initial retentive properties in case of wear of the male components. [11][12][13][14]19,24 There is a lack of studies assessing the wear of the male components of the ball attachment systems. 22 The retention loss of ball attachments has been evaluated in many clinical and laboratory studies.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This finding is aligned with previous investigations showing that significant wear of spherical abutments occurs after 8 years of wearing IODs. 24 Possible reasons for a gain in the RA attachment retention could be from work hardening of the gold matrix alloy or geometrical adaptation (plastic strain) of the matrix. Progressive loss of retention in both systems was evident during the course of the present study.…”
Section: Discussionmentioning
confidence: 99%
“…22,23 No longitudinal information is currently available regarding the wear pattern of LA abutments. 24,25 One consideration in crossover studies is the potential phase effect, which results from the order the different therapies are delivered. However, occasional gain in retention was also observed ( Table 1).…”
Section: Discussionmentioning
confidence: 99%